PENDAMPINGAN KEWIRAUSAHAAN RIAS PENGANTIN SEBAGAI PENINGKATAN KEMANDIRIAN EKONOMI PESANTREN DAN SANTRI PONDOK PESANTREN MIFTAHUL ULUM KABUPATEN JEMBER - Akhamd Haryono; ika Barokah Suryaningsih; Samudji Samudji; Fariz Kustiawan Alfarisy (Universitas Negeri Surabaya, 2021)
Jember Regency is one of the districts that is dominated by Islamic boarding schools. The majority of the figures of a kiyai are figures who also have a major influence on the development of life today. Miftahul Ulum is a boarding school located in Sidomukti Village, Mayang District, Jember Regency. The obstacle currently faced is the limited amount of make-up in Sidomukti Village and must be imported from other areas. The purpose of this service society is to improve the entrepreneurial spirit of the student through make-up in order to increase the income and skills of the student at the Islamic boarding school. The service was carried out from August - November 2020 at the Miftahul Ulum Islamic Boarding School. The service implementation method consists of several stages, namely 1) site survey, 2) FGD (Focus Group Discussion), 3) Mentoring and training, and 4) monitoring and evaluation. The achievement of the results of this service can be seen that female students can have confidence in doing make-up. Therefore the long term goal is to be able to create jobs for himself through bridal make-up.